Technical specification of 3F and 9F top steel beam, 4F and 5F Y column paint as top coat and field test report (RFA-560_Rev.B) - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of only PDF version of drawings.